2010
DOI: 10.1103/physreva.82.022901
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of the surface track potential

Abstract: Angular and energy distributions of fragment protons dissociated from HeH + during grazing-angle scattering from a KCl (001) surface are measured. The surface of KCl (001) is heated at 180 • C and the beam current is kept lower than 1 fA to prevent macroscopic surface charging. The angular distribution of the fragment protons shows a well-defined peak similarly to the grazing-angle scattering of atomic ions. The observed peak, however, is shifted from the specular angle toward larger scattering angles. The obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In our previous paper, we used a simple model to describe the surface track potential [10]. In the model, the position-dependent hole production rate was estimated using a local density binary encounter model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous paper, we used a simple model to describe the surface track potential [10]. In the model, the position-dependent hole production rate was estimated using a local density binary encounter model.…”
Section: Resultsmentioning
confidence: 99%
“…Other probing methods compatible with low beam current far below 1 pA are absolutely necessary for the detailed study on the surface track potential. Recently, we have demonstrated that HeH + ion can be used to study the surface track potential [10]. The two dimensional distributions (energy and scattering angle distributions) of fragment protons dissociated from 1-MeV HeH + during grazing angle scattering at KCl(0 0 1) were observed.…”
Section: Introductionmentioning
confidence: 98%